UNIVERSITY SERVICE WEBSITE QUALITY MEASUREMENT WITH WEBQUAL 4,0 (CASE STUDY: FACULTY OF BUSINESS AND ECONOMICS ISLAMIC UNIVERSITY OF INDONESIA) - Nur Hamid Sutanto; Kusrini Kusrini; Asro Nasiri (Jurnal Riset Informatika, 2021)
The implementation of the website as a service medium has become very popular in the developments of universities, especially during the COVID-19 pandemic, which implements health protocols. With the existence of a website-based service information system, it is possible to continue running business processes in service to users without having to come and avoid direct or face-to-face interactions. FBE UII implements a Website Service Information System to serve students online, which replaces the manual system that is served directly and face-to-face. Firstly, it is implemented until now, there has never been a measurement of the quality of service that comes from its users. The measurement used the WebQual 4.0 method which measures the user's assessment of 3 areas, namely usability, information quality, service interaction quality which affects user satisfaction with the parameter of the users using the service website. This research was conducted at the FBE UII. Research data collection used a questionnaire. The population was FBE UII students who had used the service website. The results of this study were the conclusions of successful website implementation to replace the previously used system, the quality of website-based services on information systems was good, the perception of user ratings was easy to interact with, and recommendations for strategic steps, namely migrating other services by utilizing integrated service websites.